2020
DOI: 10.1177/1012690220931736
|View full text |Cite
|
Sign up to set email alerts
|

“Helmets aren’t cool”: Surfers’ perceptions and attitudes towards protective headgear

Abstract: Studies indicate that head injuries account for a significant proportion of all surf-related injuries. Yet, despite these rates, the vast majority of surfers do not wear protective headgear. Noting both the high rate of head-related injuries and surfers’ reluctance to wear protective headgear, this sociological study sought to critically explore surfers’ perceptions and attitudes towards protective headgear, and specifically to explore why so few surfers wear protective headgear. To address these aims, the eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Of the 18 articles that were included in the final review: three focused on knowledge about and awareness of the risk of injuries to the head and injury prevention strategies (Lehl, 2005 ; Inness and Morgan, 2015 ; Jeffries et al, 2020 ), five examined perceptions of the risk of head injury and attitudes toward the use of protective headgear (Kahanov et al, 2005 ; Taylor et al, 2005 ; Provance et al, 2012 ; Tiryaki et al, 2017 ; Vriend et al, 2018 ), seven studies only examined athletes' attitudes toward using protective headgear in sport (Finch et al, 2001 , 2003 ; Pettersen, 2002 ; Braham et al, 2004 ; Ruedl et al, 2012a ,b; Pratt et al, 2019 ), two examined athletes' experiences of the obstacles to wearing protective headgear in training and competitions (Ross et al, 2010 ; Dean and Bundon, 2020 ) and one only examined the use of protective headgear in one single season (Braham and Finch, 2004 ). Finally, four studies did not include any measurement of the athletes' use of protective headgear, but the remaining 14 of the 18 studies did.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 18 articles that were included in the final review: three focused on knowledge about and awareness of the risk of injuries to the head and injury prevention strategies (Lehl, 2005 ; Inness and Morgan, 2015 ; Jeffries et al, 2020 ), five examined perceptions of the risk of head injury and attitudes toward the use of protective headgear (Kahanov et al, 2005 ; Taylor et al, 2005 ; Provance et al, 2012 ; Tiryaki et al, 2017 ; Vriend et al, 2018 ), seven studies only examined athletes' attitudes toward using protective headgear in sport (Finch et al, 2001 , 2003 ; Pettersen, 2002 ; Braham et al, 2004 ; Ruedl et al, 2012a ,b; Pratt et al, 2019 ), two examined athletes' experiences of the obstacles to wearing protective headgear in training and competitions (Ross et al, 2010 ; Dean and Bundon, 2020 ) and one only examined the use of protective headgear in one single season (Braham and Finch, 2004 ). Finally, four studies did not include any measurement of the athletes' use of protective headgear, but the remaining 14 of the 18 studies did.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies examining attitudes toward headgear identified a mismatch in attitudes, risk perception and the use of headgear (Pettersen, 2002 ; Taylor et al, 2005 ; Ruedl et al, 2012a , b ). This meant that in many cases athletes believed that wearing headgear had a protective effect in terms of reducing the number and/or severity of concussions, head injuries and/or orofacial injuries, but that athletes still chose not to wear headgear either because they felt uncomfortable wearing it (Finch et al, 2001 ; Pettersen, 2002 ; Braham et al, 2004 ; Dean and Bundon, 2020 ) or that the risk of concussion did not apply to them (Taylor et al, 2005 ). For instance, in Pettersen's ( 2002 ) study of Canadian rugby players, 62% believed that wearing headgear could prevent concussion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations